IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 72 TAHUN 2005 TENTANG DESA (Studi Kasus : Administrasi Pemerintahan Desa Nanga Taman Kecamatan Nanga Taman Kabupaten Sekadau) - Veronika Risnawati E.42009067 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
The problem is the village’s profile so hard to get, village’s secretary still not as a civil servant, there isn’t a village office and an administration management still messy. The purpose for this research is to knowing factors that influence effectivity of Implementation of Government Rule Number 72 in 2005 in Government Administration of Nanga Taman Village in Nanga Taman District Sekadau Regency still not optimal. This research using descriptive research with qualitative paradigm. The technics of data collecting using interview technic, observation technic and documentation technic. The conclusion of this research is the factors such as communication, resources, disposition and bureaucracy structure influence effectivity of Implementation of Government Rule Number 72 in 2005 in Government Administration of Nanga Taman Village in Nanga Taman District Sekadau Regency and make it not optimal. The peoples need to do are such as increase the village worker quality, giving a material about task and function of village worker and increase communication also transparency the village worker with peoples. Keyword : implementation, communication, resources, disposition and bureaucracy structure.